Design and Build a Mini Aquaponic Smart System for Subtropical Plants Based on the Internet of Things (IOT) - Hidayat, Arief; Rochman, Sagita (Universitas PGRI Adi Buana Surabaya, 2024)
As a country with a tropical climate, Indonesia stands out as a land rich in various types of animals and plants. The diversity of climates and environments provides fertile habitats, enabling the survival of various species that adorn Indonesia's natural beauty. To fulfill the desires of subtropical plant lovers whose hobby is agriculture, researchers have the idea of creating a research automatic planting system that can be used to grow subtropical plants in urban areas. The ESP32 acts as a monitoring device that produces vital information regarding environmental conditions, such as soil moisture, water acidity levels, and feed supplies in a system. Through this monitoring, research can collect relevant data to analyze conditions and optimize these factors. The data obtained will be processed and analyzed through daily development comparisons. The existence of intelligent systems, such as monitoring water pH and humidity, providing fish food, and regulating the water content in ponds and hydroponic growing media, can make it easier for those who want to develop farming and fish farming hobbies in urban areas where land is limited and busy with activity.